A Novel Approach to Improve the Estimation of a Diet Adherence Considering Seasonality and Short Term Variability – The NU-AGE Mediterranean Diet Experience - Giampieri, Enrico; Ostan, Rita; Guidarelli, Giulia; Salvioli, Stefano; Berendsen, Agnes A. M.; Brzozowska, Anna; Pietruszka, Barbara; Jennings, Amy; Meunier, Nathalie; Caumon, Elodie; Fairweather-Tait, Susan; Sicinska, Ewa; et al. (Frontiers in Physiology, 2019)
In this work we present a statistical approach to improve the assessment of the adherence to a one-year nutritional intervention within the framework of the NU-AGE project. This was measured with an adherence score based on 7-days food records (7DFR), under limitations on the number of observations per subject and time frame of intervention. The results of the NU-AGE dietary intervention were summarized by variations of the NU-AGE index as described in the NU-AGE protocol. Food and nutrient intake of all participants was assessed by means of 7DFR at recruitment and after 10 to 14 months of intervention. Sixteen food groups and supplementations have been used to estimate the NU-AGE index before and after the intervention. The 7DFR is a reliable tool to register food intakes, however, as with other tools used to assess lifestyle dietary compliance, it is affected by uncertainty in this estimation due to the possibility that the observed week is not representative of the entire intervention period.. Also, due to logistic limitations, the effects of seasonality can never be completely removed. These variabilities, if not accounted for in the index estimation, will reduce the statistical power of the analyses. In this work we discuss a method to assess these uncertainties and thus improve the resulting index. The proposed method is based on Hierarchical Bayesian Models. This model explicitly includes country-specific averages of the NU-AGE index, index variation induced by the dietary intervention, and country based seasonality. This information is used to evaluate the NU-AGE index uncertainty and thus to estimate the “real” NU-AGE index for each subject, both before and after the intervention. These corrections reduce the possibility of misinterpreting measurement variability as information, improving the power of the statistical tests that are performed with the resulting index. The results suggest that this method is able to reduce the short term and seasonal variability of the measured index in multicenter dietary intervention trials. Using this method to estimate seasonality and variability would allow one to obtain better measurements from the subjects of a study, and be able to simplify the scheduling of diet assessments.